Effect and safety of interferon for hepatocellular carcinoma: a systematic review and meta-analysis. - Liping Zhuang; Xiantao Zeng; Zongguo Yang; Zhiqiang Meng (PLoS ONE, 2013)
Background The effect of interferon(IFN) in the management of hepatocellular carcinoma (HCC) remains controversial, and no clear recommendations have been proposed. Objectives To evaluate the effect and safety of IFN for HCC. Methods PubMed, OvidSP, and Cochrane Library were searched from their establishment date until August 30, 2012. Studies that met the inclusion criteria were systematically evaluated and then subjected to meta-analysis. Results Thirteen randomized control trials (RCTs) involving 1344 patients were eligible for this study. When IFN was used as an adjuvant therapy for HCC patients after curative therapy, the meta-analysis showed that IFN reduced the 1-, 2-, 3-, 4-, and 5-year recurrence rates. Subgroup analysis showed that IFN reduced the 2-, 3-, 4-, and 5-year recurrence rates of hepatitis C viral (HCV)-related HCC. The effect of IFN for on hepatitis B virus(HBV)-related HCC patients could not be determined because of isufficient data. After surgical resection, adjuvant IFN therapy reduced the 4- and 5- recurrence rates. All studies reported that IFN could not improve the overall survival of HCV-realated HCC patients after curative therapies. Only one study showed that IFN was associated with better overall survival in HCC patients after curative therapy and subgroup of HCC patients after surgical resection. Thus, meta-analysis was not performed. Different treatment options were used as control to study the effect of IFN for intermediate and advanced HCC patients, thus meta-analysis was not appropriate. All included studies, except for one, reported that IFN treatment was well tolerated. Conclusions After curative therapies, adjuvant IFN reduced the recurrence of HCC. IFN did not improve the survival of HCV-related HCC patients after curative therapy. Whether IFN is effective for intermediate and advanced HCC patients could not be determined because of insufficient data. The toxicity of IFN was acceptable.